Lung mast cells in rats exposed to acute hypoxia, and chronic hypoxia with recovery. Issue 3 (June 1977) - Williams, A; Heath, D; Kay, J M; Smith, P
Abstract : Exposure to acute hypoxia (barometric pressure 263 mmHg) for 8 hours did not lead to increased numbers of mast cells in the lungs of rats. In contrast, in adult rats kept for 35 days at a barometric pressure of 380 mmHg there was a proliferation of mast cells around the pulmonary blood vessels and in the alveolar septa. This hyperplasia of lung mast cells in response to chronic hypoxia was reversible on removal of the hypoxic stimulus. There was a correlation between the logarithm of the perivascular lung mast cell density (defined in the paper) and the logarithm of the right ventricular weight. There was no increase in the mast cells in the carotid bodies of the hypoxic rats. Young male, old male, young female, and old female rats which had been subjected for 39 days to a barometric pressure of 380 mmHg showed a proliferation of mast cells around the pulmonary blood vessels and in the alveolar walls. This response was greatest in the adult animals and independent of their sex. In the age and sex experiment there was a correlation between the perivascular lung mast cell density and the medial thickness of the muscular pulmonary arteries. Since mast cell hyperplasia has been reported as preceding right ventricular hypertrophy, it is conceivable that mast cell proliferation in the lung may be a defence mechanism to limit the severity of hypoxic pulmonary hypertension rather than to mediate it.